1993
DOI: 10.1111/j.1748-1716.1993.tb09481.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin contracts human uterine myometrium by a partly dihydropyridine‐sensitive mechanism

Abstract: The effect of endothelin (ET), a recently discovered 21-amino-acid polypeptide with powerful vasoconstrictor properties, was examined on human uterine myometrial strips in vitro. ET dose-dependently (10(-11)-10(-7) M) increased the contractile force (monitored as contraction amplitude) of the myometrium with significant effects at 10(-8) and 10(-7) M. ET (10(-8) M and up) also increased the basal tone of the myometrium. The calcium channel blocking agents nifedipine (10(-7) M) and diltiazem (10(-6) M) both inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A series of studies has already suggested that KCl induces contractions through voltage-dependent Ca ++ influx, which is completely abolished by the presence of voltage-dependent Ca ++ channel blockers, such as nifedipine and verapamil (Izumi et al 1995). In the case of ET1, the dominant requirement and the final event leading to uterine contractility is the increase in the intracellular level of calcium ) which is realized, however, not only through voltage-dependent Ca ++ influx, but also through release of Ca ++ from intracellular pools and sustained entry of Ca ++ from receptoroperated Ca ++ channels , Fried et al 1993. The latter involves a cascade of events including activation of phospholipase C and A and some isoforms of protein kinase C (Xuan et al 1994, Tertrin-Clary et al 1999.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies has already suggested that KCl induces contractions through voltage-dependent Ca ++ influx, which is completely abolished by the presence of voltage-dependent Ca ++ channel blockers, such as nifedipine and verapamil (Izumi et al 1995). In the case of ET1, the dominant requirement and the final event leading to uterine contractility is the increase in the intracellular level of calcium ) which is realized, however, not only through voltage-dependent Ca ++ influx, but also through release of Ca ++ from intracellular pools and sustained entry of Ca ++ from receptoroperated Ca ++ channels , Fried et al 1993. The latter involves a cascade of events including activation of phospholipase C and A and some isoforms of protein kinase C (Xuan et al 1994, Tertrin-Clary et al 1999.…”
Section: Tablementioning
confidence: 99%
“…It has been reported that the binding sites for ET1 are distributed in the human uterus throughout the menstrual cycle (O'Reilly et al 1992) and that both subtypes of receptors are localized in human myometrium, where ETA binding sites represent the principal subtype (Schiff et al 1993, Breuiller-Fouche et al 1994, Pekonen et al 1994, Wolff et al 1996. It has been demonstrated that in human nonpregnant myometrium, ET1 induces contractions , Fried et al 1993, Svane et al 1993 activating exclusively the ETA receptors, and increasing the two phases of spontaneous myometrial contractility, the phasic and the tonic phase, despite the lesser sensitivity of nonpregnant compared with pregnant myometrium (Word et al 1991, Osada et al 1997. Although binding studies have shown that ET1 exhibits affinity for ETB receptors, activation of ETB sites, using ETB selective ligands, has not been reported to mediate any contractile effect on human myometrial tissue; the lack of any contractile effect on human nonpregnant uterus has been attributed to the small population of ETB receptors (less than 25%) on human myometrium, or to their involvement in mechanisms of relaxation and proliferation; the precise role of ETB subtypes of receptors in human uterus needs to be further elucidated (Maggi et al 1994, Bacon et al 1995, Heluy et al 1995, Wolff et al 1996, Osada et al 1997.…”
Section: Introductionmentioning
confidence: 99%